Sensitivity of Temperate Desert Steppe Carbon Exchange to Seasonal Droughts and Precipitation Variations in Inner Mongolia, China - Yang, Fulin (Public Library of Science, 2013)
Arid grassland ecosystems have significant interannual variation in carbon exchange; however, it is unclear how environmental factors influence carbon exchange in different hydrological years. In this study, the eddy covariance technique was used to investigate the seasonal and interannual variability of CO(2) flux over a temperate desert steppe in Inner Mongolia, China from 2008 to 2010. The amounts and times of precipitation varied significantly throughout the study period. The precipitation in 2009 (186.4 mm) was close to the long-term average (183.9±47.6 mm), while the precipitation in 2008 (136.3 mm) and 2010 (141.3 mm) was approximately a quarter below the long-term average. The temperate desert steppe showed carbon neutrality for atmospheric CO(2) throughout the study period, with a net ecosystem carbon dioxide exchange (NEE) of −7.2, −22.9, and 26.0 g C m(−2) yr(−1) in 2008, 2009, and 2010, not significantly different from zero. The ecosystem gained more carbon in 2009 compared to other two relatively dry years, while there was significant difference in carbon uptake between 2008 and 2010, although both years recorded similar annual precipitation. The results suggest that summer precipitation is a key factor determining annual NEE. The apparent quantum yield and saturation value of NEE (NEE(sat)) and the temperature sensitivity coefficient of ecosystem respiration (R(eco)) exhibited significant variations. The values of NEE(sat) were −2.6, −2.9, and −1.4 µmol CO(2) m(−2) s(−1) in 2008, 2009, and 2010, respectively. Drought suppressed both the gross primary production (GPP) and R(eco), and the drought sensitivity of GPP was greater than that of R(eco). The soil water content sensitivity of GPP was high during the dry year of 2008 with limited soil moisture availability. Our results suggest the carbon balance of this temperate desert steppe was not only sensitive to total annual precipitation, but also to its seasonal distribution.